Analisis Performa Pembangkit Listrik Panas Matahari Menggunakan Generator Termoelektrik - Abdurrasyid, Faris; Margianto; Nur Robbi (RING ME, 2023)
In Indonesia, non-renewable fossil fuels are used to produce electrical energy which has the potential to impact the environment. Renewable energy is needed as an energy source to reduce consumption of fossil fuels. Solar thermal is one of the abundant energy sources in Indonesia, and thermoelectric generators can be used to make use of it. A thermoelectric generator can generate electricity from the sun's abundant heat energy and does not damage the environment by using a solar collector on the hot side and a heatsink on the cold side. This study aims to determine the performance of thermoelectric generators, heatsinks, solar collectors and the overall efficiency of the device. The findings of this study indicate that the energy output obtained by the collector due to variations in the sun affects the efficiency of the solar collector on the hot side of the thermoelectric generator. The efficiency of a heatsink located on the cold side of a thermoelectric generator is inversely proportional to its base heat value. The value of the temperature difference on the hot and cold sides of the thermoelectric generator fluctuates, which affects the efficiency value of the thermoelectric generator, while the useful energy and power produced by the thermoelectric generator can affect the efficiency of the system as a whole.